Reproduksi Seksual Karang Scleractinia: Telaah Pustaka - Bachtiar, Imam (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2003)
There has been a revolutioner development in our understanding about coral reproduction in the middle of 1980s. All publication, before this period, therefore provides incomplete facts and wrong conclusions about the modes of coral reproduction. Most corals are hermaphodite and broadcast spawners, in which fertilization takes place externally. Temperature, photoperiod, lunar and tidal cycles are thought to be major environmental factors influencing reproductive cycle in corals. In Indonesia, sexual pattern of scleractinian corals consistent with previously reported data from other regions. Available data show that multispecific spawning may occurs in Indonesia. There are also some evidences that there is variation in spawning season between corals in Lombok and Karimunjawa Islands.